2006
DOI: 10.1002/art.21678
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of joint damage in patients with early rheumatoid arthritis treated with high‐dose methotrexate with or without concomitant infliximab: Results from the ASPIRE trial

Abstract: Objective. To identify disease characteristics leading to progression of joint damage in patients with early rheumatoid arthritis (RA) treated with methotrexate (MTX) versus those treated with infliximab plus MTX.Methods. Patients who had not previously been treated with MTX with active RA were randomly assigned to receive escalating doses of MTX up to 20 mg/week plus placebo or infliximab at weeks 0, 2, and 6, and every 8 weeks thereafter through week 46. Radiographic joint damage was assessed using the modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
262
8
18

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 404 publications
(304 citation statements)
references
References 38 publications
16
262
8
18
Order By: Relevance
“…In general, the reduction in CRP and ESR levels correlate with a decrease in clinical disease activity (32) and less joint destruction (33), although this may be due, in part, to the direct systemic effect of TNFi on hepatic synthesis of acute-phase proteins rather than a true improvement in local synovitis. In fact, CRP level is an important biomarker of radiographic progression in RA patients receiving DMARDs (methotrexate), but this predictive value disappears when RA patients are treated with TNFi (34). Moreover, calprotectin serum levels significantly decrease after TNFi treatment and are independently associated with radiographic progression in RA (14,17).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the reduction in CRP and ESR levels correlate with a decrease in clinical disease activity (32) and less joint destruction (33), although this may be due, in part, to the direct systemic effect of TNFi on hepatic synthesis of acute-phase proteins rather than a true improvement in local synovitis. In fact, CRP level is an important biomarker of radiographic progression in RA patients receiving DMARDs (methotrexate), but this predictive value disappears when RA patients are treated with TNFi (34). Moreover, calprotectin serum levels significantly decrease after TNFi treatment and are independently associated with radiographic progression in RA (14,17).…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated that a simple cortisol and ACTH measurement can help to further guide anti-TNF antibody treatment. This is particularly relevant because important parameters such as CRP level, ESR, and swollen joint count are not predictive in RA patients treated with anti-TNF antibodies plus methotrexate (18). We suggest that inclusion of cortisol and ACTH and their respective molar ratio in the decision-making process can help to determine the appropriateness of anti-TNF therapy in patients with RA.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent clinical trials evaluated whether the combination of a DMARD and an anti-TNFα agent was superior to either agent alone [11,12] or compared an anti-TNF agent with placebo [13,14]. Emboldened by the positive results of these trials, investigators probed a window of opportunity by asking whether treating patients with an anti-TNF agent in early stages (less than 3 years) of disease could 'wipe out' the disease and provide long-lasting remissions [12,[15][16][17].…”
Section: Joint Inflammationmentioning
confidence: 99%